Prospects of Business and Entrepreneurship of the Danube Region (Ukraine) in the Context of European Integration - Tetyana Vdovenko (Journal of Danubian Studies and Research, 2023)
Ukraine, its civil and business community found themselves in extremely difficult circumstances and challenges due to the military actions launched in February 2022. And those processes, transformations that took place before these sad events in the economic situation in Ukraine related to the rapprochement, integration of Ukrainian business into the European economic space have received a new development. The article considers the concept and essence of such categories as business and entrepreneurship, describes practical plane of business in Ukraine in the historical aspect of business development and geographically. Initially, business and entrepreneurship in Ukraine went autonomously from those economic processes that took place in Europe. Business itself in Ukraine also developed differently in different regions.